Three-dimensional numerical investigation on melting performance of phase change material composited with copper foam in local thermal non-equilibrium containing an internal heater. (May 2021) - Zhang, Xiaochun; Su, Guokai; Lin, Junjiang; Liu, Aihua; Wang, Changhong; Zhuang, Yijie
Highlights: 3D melting performance of CPCM in the LTNE state inside an internal heated porous cavity is numerically investigated. Increasing Ra enhances convective heat transfer in the upper part of the porous cavity. Temperature distribution of low Da is dominated by heat conduction in porous media at the later melting stage. Increase of heater volume size can enhance the LHTES performance. Abstract: This work aims to numerically study the 3D melting heat transfer of latent heat thermal energy storage (LHTES) systems with phase change material (PCM) embedded in copper foam inside an internal heated cubic cavity. The enthalpy-porosity method to model the phase change process is employed and the Darcy-Forchheimer law and local thermal non-equilibrium (LTNE) model are assumed for the metal foam. The numerical code of proposed model shows good agreement for copper foam composited PCM melting with carefully designed experiments. Special attentions are given to detect the effects of Rayleigh number (Ra), porosity ( ε ), Darcy number (Da) and heater size on evolvement of solid-liquid interface, temperature stratification and full melting. The results show that increasing Ra enhances convective heat transfer in the upper part of the porous cavity; though the completely melting time remains almost unchanged. For a fixed porosity, decrease of Da reduces the melting rate in the medium melting stage, and the temperature distribution of low Da is dominated by the heat conduction in porous media at the later stage, but Da shows a negligible effect on the complete melting time. For a fixed Da, increase of porosity decelerates the complete melting time. Apart from that, the heater size also plays an important role in the melting performance of composited PCM.